Factors contributing to research team effectiveness: testing a model of team effectiveness in an academic setting - Omar, Zoharah; Ahmad, Aminah (Sciedu Press, 2014)
Following the classic systems model of inputs, processes, and outputs, this study examined the influence of three input factors, team climate, work overload, and team leadership, on research project team effectiveness as measured by publication productivity, team member satisfaction, and job frustration. This study also examined the mediating effect of a process factor, team commitment. The sample comprised 292 faculty members of four research universities in Malaysia. The respondents were asked to consider one research project in which they were involved either as a project leader or team member when completing the questionnaire. The results of the study demonstrated that there were direct relationships only between work overload and job frustration and between team leadership and team member satisfaction. Team commitment had a full or partial mediation effect on the relationships between team climate, work overload, and team leadership and research project team effectiveness. These findings suggest that different input factors influence different aspects of team effectiveness and that team climate is a key input factor that influences team effectiveness through team commitment as a process factor in an academic setting. The results of this study provide a potentially useful framework following the classical systems model of input-process-output for the establishment of effective research project teams in an academic setting.